Scopolamine and MK-801 impair recognition memory in a new spontaneous object exploration task in monkeys - Oliveira, André W.C.; Pacheco, Jéssica V.N.; Costa, Clara S.; Aquino, Jéssica; Maior, Rafael S.; Barros, Marilia (Pharmacology, biochemistry and behavior, 2021)
The spontaneous object recognition (SOR) task is one of the most widely used behavioral protocols to assess visual memory in animals. However, only recently was it shown that nonhuman primates also perform well on this task. Here we further characterized this new monkey recognition memory test by assessing the performance of adult marmosets after an acute systemic administration of two putative amnesic agents: the competitive muscarinic acetylcholine receptor antagonist scopolamine (SCP; 0.05 mg/kg) and the noncompetitive N-methyl-d-aspartate glutamate receptor antagonist MK-801 (0.015 mg/kg). We also determined whether the acetylcholinesterase inhibitor donepezil (DNP; 0.50 mg/kg), a clinically-used cognitive enhancer, reverses memory deficits caused by either drug. The subjects had an initial 10 min sample trial where two identical neutral objects could be explored. After a 6 h retention interval, recognition was based on an exploratory preference for a new rather than familiar object during a 10 min test trial. Both SCP and MK-801 impaired the marmosets' performance on the SOR task, as both objects were explored equivalently. Co-administration of 0.50 mg/kg of DNP reversed the SCP- but not the MK-801-induced memory deficit. These results indicate that cholinergic and glutamatergic pathways mediate object recognition memory in the monkey SOR task. •SCP and MK-801 impaired object recognition memory in the monkey SOR task.•DNP reversed SCP- but not MK-801-induced SOR memory deficits.•Cholinergic and glutamatergic pathways mediate recognition memory in marmosets.